2022
DOI: 10.3390/buildings12091309
|View full text |Cite
|
Sign up to set email alerts
|

Application of LightGBM Algorithm in the Initial Design of a Library in the Cold Area of China Based on Comprehensive Performance

Abstract: The proper application of machine learning and genetic algorithms in the early stage of library design can obtain better all-around building performance. The all-around performance of the library, such as indoor temperature, solar radiation, indoor lighting, etc., must be fully considered in the initial design stage. Aiming at building performance optimization and based on the method of “generative design”, this paper constructs the library’s comprehensive performance evaluation workflow and rapid prediction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The LightGBM algorithm is capable of aggregating distinct attributes into a consolidated features, which may be utilized to construct histograms that categorize similar attributes [ 100 ]. The objective of the LightGBM algorithm, when applied to a supervised dataset X , is to identify an estimation of the function that reduces the expected value of a chosen loss function [ 101 ]: …”
Section: Materials and Methodsmentioning
confidence: 99%
“…The LightGBM algorithm is capable of aggregating distinct attributes into a consolidated features, which may be utilized to construct histograms that categorize similar attributes [ 100 ]. The objective of the LightGBM algorithm, when applied to a supervised dataset X , is to identify an estimation of the function that reduces the expected value of a chosen loss function [ 101 ]: …”
Section: Materials and Methodsmentioning
confidence: 99%
“…Regarding energy conservation, these standards underscore the principle of prioritizing passive energy conservation and advocates for maximizing natural ventilation to enhance the thermal insulation performance of the building envelope structure. Widely acknowledged within the academic community of building energy conservation research in China, this standard serves as a significant academic point of reference for scholars engaged in simulation studies [61], as shown in Table 3.…”
Section: Building Envelope Parameter Se Ingmentioning
confidence: 99%
“…It has found applications in various domains, including medicine [28], economy [34], and agriculture [35]. LightGBM is a gradient-boosting framework that uses tree-based learning algorithms and relies on a loss function that measures the discrepancy between the predicted and the actual values of the target variable [36,37].…”
Section: Light Gradient-boosting Machine (Lightgbm)mentioning
confidence: 99%